2022
DOI: 10.21037/qims-22-127
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue water in patients with severe sepsis affects tissue oxygenation measured by near-infrared spectroscopy: a prospective, observational case-control study

Abstract: Background: Tissue oedema affects tissue perfusion and interferes with the monitoring of tissue oxygenation in patients with severe sepsis. However, the underlying mechanisms remain unclear. We used a wireless near-infrared spectroscopy (NIRS) device that transmits tri-wavelength light to quantify tissue haemoglobin (Hb) and water (H 2 O) content. We estimated tissue H 2 O in severe sepsis patients and healthy controls, compared their difference, and investigated the correlation of tissue H 2 O with systemic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Understanding the state of tissue uid is necessary to prevent the harm of uid overload on microcirculation and may guide uid therapy and prevent liberal uid administration. To estimate the accumulated tissue uid, we developed a NIRS device to detect tissue H 2 O and found that [H 2 O] was signi cantly higher in patients with severe sepsis than in healthy controls (21). In the present research, we discovered that oliguric patients with severe sepsis had more positive uid balance and gradually accumulated H 2 O in the tissues.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Understanding the state of tissue uid is necessary to prevent the harm of uid overload on microcirculation and may guide uid therapy and prevent liberal uid administration. To estimate the accumulated tissue uid, we developed a NIRS device to detect tissue H 2 O and found that [H 2 O] was signi cantly higher in patients with severe sepsis than in healthy controls (21). In the present research, we discovered that oliguric patients with severe sepsis had more positive uid balance and gradually accumulated H 2 O in the tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Adult patients (aged ≥ 18 years) who were transferred to the ICU from the emergency department and admitted within 72 h for new-onset severe sepsis were enrolled. The detailed eligibility criteria were described in our previous report (21). After signing the informed consent, the patients were assessed with a non-invasive wireless NIRS device, which is still investigational, for three consecutive days.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a constantly growing interest among researchers in the possibility of using NIRS in monitoring changes in muscle oxygenation and blood flow during physiological and pathological conditions, e.g., during submaximal and maximum exercise [13,[20][21][22], to identify peripheral vascular disease [23], in chronic obstructive pulmonary disease (COPD) [24], in cardiovascular diseases [25] and in sepsis [26]. It has been found that during work the degree of deoxidation of skeletal muscles varies depending on the type of muscle, type of exercise and blood flow specific to a given area and health status [27,28].…”
Section: Introductionmentioning
confidence: 99%